Penerapan Supervisi Akademik Untuk Meningkatkan Kompetensi Guru dalam Menyusun Administrasi Penilaian Di SDN 31/IX Sei Landai Muaro Jambi - Sudiah Sudiah (Jurnal Ilmiah Dikdaya, 2021)
This study aims to improve the pedagogical competence of teachers in preparing assessment administration through academic supervision. In this research, the type of research used is school action research. This research consists of the stages of planning the action, implementing the action, observing, and reflecting. Class observation technique used in data collection techniques. The teacher ability assessment tool (APKG) is in the form of a learning administration assessment instrument using an observation instrument. The comparative descriptive analysis technique is used in analyzing the data by describing it in words or explaining the quantitative data obtained. The results showed that academic supervision could improve the ability of teachers to arrange administrative assessments in learning at SDN 31 / IX Sei Landai by 26.2% as indicated in the results of the study.